The Opportunities of the Merdeka Curriculum for Developing Early Childhood Education Teachers’ Competencies in the Society 5.0 Era: A Literature Review - Chika Khaylah Doritha (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The implementation of the Independent Curriculum provides various opportunities to improve the competence of Early Childhood Education (PAUD) teachers in responding to educational challenges in the era of Society 5.0. However, previous studies generally examined curriculum implementation, pedagogical competence, professional development, and digital literacy separately. Therefore, this study aims to analyze the opportunities offered by the Independent Curriculum in developing the competence of PAUD teachers in the era of Society 5.0. This study uses a qualitative approach with library research methods. Data were collected through documentation techniques from scientific journals, books, research reports, proceedings, and educational policy documents relevant to the topics of the Independent Curriculum, teacher competence, and Society 5.0. Data were analyzed using content analysis through data reduction, data presentation, interpretation, and drawing conclusions. The results of the study reveal four main opportunities provided by the Independent Curriculum in developing the competence of PAUD teachers: pedagogical, professional, digital, and social competence. This curriculum promotes child-centered and differentiated learning, strengthens teachers' professional capacity through curriculum planning and assessment development, enhances digital literacy and technology integration in learning, and encourages collaboration between teachers, parents, and the community. These findings suggest that the Independent Curriculum serves not only as an education policy reform but also as a strategic framework for strengthening the competencies of early childhood education (PAUD) teachers to meet the demands of Society 5.0. However, these findings are limited to literature-based evidence and require further empirical investigation.